ChemInform Abstract: A Nitrate Nonlinear Optical Crystal Pb16(OH)16(NO3)16 with a Large Second‐Harmonic Generation Response. Issue 24 (2nd June 2014) - Chang, Lixian; Wang, Li; Su, Xin; Pan, Shilie; Hailili, Reshalaiti; Yu, Hongwei; Yang, Zhihua
Abstract Colorless block crystals of the title compound are hydrothermally prepared from aqueous mixtures of Pb(NO3)2 and LiOOH (autoclave, 200 °C, 72 h, 92% yield).